2010
DOI: 10.1530/rep-10-0178
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanism underlying cyclic changes in mouse uterine bicarbonate secretion: role of estrogen

Abstract: Our previous study has demonstrated that bicarbonate in the uterine fluid plays an indispensable role in sperm capacitation. However, the cellular mechanisms underlying the formation of bicarbonate-rich uterine fluid and the regulatory mechanism remained largely unknown. In this study, the expression profiles of bicarbonate transport/production proteins, the cystic fibrosis transmembrane conductance regulator (CFTR), SLC26A6, carbonic anhydrase 2 (CAR2, CA2) and CAR12 (CA12), throughout the estrous cycle, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 29 publications
6
36
1
Order By: Relevance
“…In fact, we have demonstrated that ectopic high concentration of E 2 (10 mg/mL) dramatically induced apoptosis in cultured endometrial epithelial cells, which can be completely abolished by the CFTR inhibitor, indicating that CFTR mediates supraphysiologic E 2 -induced apoptosis in the endometrial epithelial cells. On the other hand, recent studies into the role of CFTR in female reproductive health and disease have made it clear that CFTR plays a key role in regulating female sex hormone responsive fluid volume and composition, and that aberrant upregulation of CFTR expression by high concentrations of E 2 may lead to disturbance of the fluid environment resulting in various pathological conditions (18,19,43,44). To our surprise, we did not observe significant ovarian fluid accumulation during implantation in the COH model.…”
Section: Figurecontrasting
confidence: 53%
See 1 more Smart Citation
“…In fact, we have demonstrated that ectopic high concentration of E 2 (10 mg/mL) dramatically induced apoptosis in cultured endometrial epithelial cells, which can be completely abolished by the CFTR inhibitor, indicating that CFTR mediates supraphysiologic E 2 -induced apoptosis in the endometrial epithelial cells. On the other hand, recent studies into the role of CFTR in female reproductive health and disease have made it clear that CFTR plays a key role in regulating female sex hormone responsive fluid volume and composition, and that aberrant upregulation of CFTR expression by high concentrations of E 2 may lead to disturbance of the fluid environment resulting in various pathological conditions (18,19,43,44). To our surprise, we did not observe significant ovarian fluid accumulation during implantation in the COH model.…”
Section: Figurecontrasting
confidence: 53%
“…In addition to its wellestablished ion channel function, CFTR has been proposed to have many other roles that either directly or indirectly impact various cellular functions, including apoptosis (13,14). Previous studies from both our laboratory and that of other investigators have revealed that the expression of uterine CFTR changes with the estrous cycle (15)(16)(17)(18)(19). In addition, stimulation of CFTR expression by estrogen (E) both in vivo and in vitro (20,21) has also been demonstrated and down-regulation of CFTR by P reported (22).…”
mentioning
confidence: 95%
“…Studies on both rodents and humans have revealed that the expression of CFTR in the female reproductive tract is enhanced by oestrogens and suppressed by progesterone in vitro or in vivo. 23,[103][104][105][106][107][108][109] In airway cells, b-oestradiol was found to promote CFTR protein maturation by upregulating the CFTR-interacting protein Na + /H + exchanger regulatory factor (NHERF) 1. 110 A recent study using nucleosome mapping across the CFTR locus identified the glucocorticoid receptor as a trans-acting factor regulating CFTR transcription.…”
Section: Environment-dependent Cftr Expressionmentioning
confidence: 99%
“…Furthermore, CFTR is also known to be involved in bicarbonate transport either directly [53] or indirectly [54], which is important for activation of cAMPdependent signaling pathway [53,55] in addition to pH regulation. In the last decade, various studies from our laboratory have demonstrated that normal function of CFTR and/or ENaC is critical for a variety of reproductive events such as sperm capacitation [53,56] and implantation [57,58], defects or dysregulation of which lead to a number of pathological conditions, such as ovarian hyperstimulation syndromes, hydrosalpinx and infertility [44,59]. These observations suggest that ion channels/transporters may respond to microenvironmental changes and play an important role in various physiological and pathological processes.…”
Section: Ion Channels/transporters and Their Crosstalk With The Micromentioning
confidence: 99%